Artists' techniques ([London] Open University/BBC, 1993)
Examines five paintings: Gleyre's Lost Illusions, Renoir's La Parisienne, Manet's Dejeuner sur l'Herbe, Monet's Autumn at Argenteuil, and Cezanne's Mountains Seen from l'Estaque, for the techniques which each artist employed.
VHS format.
Director, Tony Coe ; presenter/writer, Anthea Callen.
Keywords: Painting -- Technique; Artists' materials